Molecular characterization and transcriptomic analysis of a novel polymycovirus in the fungus Talaromyces amestolkiae - Teng, Li; Chen, Sen; Hu, Zuquan; Chen, Jili; Liu, Hongmei; Zhang, Tingting (Frontiers in Microbiology, 2022)
Talaromyces amestolkiae is an important fungal species because of its ubiquity which was isolated from soil, plants, sponges, and foods. Here, we identified a novel six-segmented polymycovirus, Talaromyces amestolkiae polymycovirus 1 (TaPmV-1). Each dsRNA contains a single open reading frame. The proteins encoded by dsRNA1, dsRNA 2, dsRNA 3 and dsRNA 5 shared signiﬁcant amino acid identities of 56%, 40%, 47% and 43% with the corresponding proteins of Aspergillus fumigatus polymycovirus-1. DsRNA1, 3, and 5 of TaPmV-1 encoded an RNA-dependent RNA polymerase, a viral methyltransferase, and a P-A-S-rich protein, respectively. The function of proteins encoded by the dsRNA2, dsRNA4 and dsRNA5 were unknown. TaPmV-l infection may be decreased the production of red pigments and result in clustered together of sclerotia by comparing virus-infected strain LSH3 with virus-cured strain LSHVF. Furthermore, transcriptomic analysis showed that TaPmV-l infection caused the down-regulation of transcripts related to metabolism may correlate with reduced the production of red pigments and resulted in got together of sclerotia in T.amestolkiae. These results of this study provide further insights into the mechanism of fungal gene regulation by polymycovirus infection at the transcriptome level. In addition, to our knowledge, this is the first report of a mycovirus in T.amestolkiae.